From "postcolonialism to" postoccidentalism ": a reading from Latin American and Andean historicity - Pajuelo, Ramón (2016)
This article offers a review and critical analysis of the contributions and perspectives of postcolonial/postoccidental studies. Through a discussion of the recent works of the principal representatives of postcolonial/postoccidental studies (Walter Mignolo, Fernando Coronil, Anlbal Qui-jan o, Enrique Dussel, Santiago Castro-Gómez, Edgardo Lander, etc.), the article explores the problems related to the reception of these studies and their heoretical implications within a particular space of historicity: Latin America and specifically the Andean region